Classification of the rotational shot-put based on duration time of motion phases - Kato, T.; Maeda, K.; Ismail, S. I. (ISBS Proceedings Archive (Michigan), 2020)
This study aimed to investigate the relationships between throwing distance and duration times of motion phases in the rotational shot-put and attempted to classify the throw based on duration times. A total of 181 recorded trials performed by male shot-putters were obtained, and their duration time and the ratio of duration time of defined motion phases were analysed. Duration time and the ratio of duration time were not correlated with throwing distance for all motion phases. Result of a cluster analysis indicated that athletes could be classified in two groups and there were significant differences in duration time at initiation and later phases between the groups. As a result, it is suggested that the changes in duration time might not influence the throwing distance. In addition, it was identified that there are two kinds of group based on the duration times in the rotational shot-put.